Gaming the Iron Curtain : How Teenagers and Amateurs in Communist Czechoslovakia Claimed the Medium of Computer Games - Švelch, Jaroslav (Book collections on Project MUSE., 2018)
"Based on oral histories gathered from players, game creators and hobbyists active in the 1980s, as well as archival material like computer club newsletters, official documents, hobby magazines, TV broadcasts and the games produced in the period, Gaming the Iron Curtain offers a social history of games in Communist-era Czechoslovakia - a country with a rigid centrally planned economy, separated from its Western neighbors by the so-called Iron Curtain. In Czechoslovakia at the time, there was no hardware or software market, no private enterprise, no commercial advertising and no publicly available computing or gaming magazines. Despite these limitations, a vibrant computer hobby scene emerged. Tens of thousands of Czechs and Slovaks played computer games and at least two hundred titles were developed over the course of the 1980s. Aside from playing games, Czechoslovak home computer enthusiasts were also "gaming" their hardware and software by discovering new ways to code, crack and hack. But most importantly, they looked for and took advantage of 'gaps' in the Iron Curtain and the oppressive political regime in order to play and create games. Gaming the Iron Curtain therefore an original historical narrative as well as a comprehensive social historical understanding of how computer games were made and how gaming communities functioned in the Soviet bloc"--